Clear cell sarcoma of kidney involving a horseshoe kidney and harboring EGFR internal tandem duplication. Issue 11 (25th April 2017) - Santiago, Teresa; Clay, Michael R.; Azzato, Elizabeth; Newman, Scott; Fernandez‐Pineda, Israel; Nichols, Kim E.; Zhang, Jinghui; Downing, James R.; Davidoff, Andrew; Brennan, Rachel C.; Ellison, David W.
Abstract: Clear cell sarcoma of kidney (CCSK) is a rare renal malignancy, previously unreported in horseshoe kidney (HSK). B‐cell lymphoma 6 corepressor ( BCOR ) gene internal tandem duplication (ITD) was identified as a recurrent somatic alteration in approximately 85% of CCSKs. This and the YWHAE–NUTM2B/E fusion, the second most common recurrent molecular alteration in CCSK (10%), are considered to be mutually exclusive. However, there is a subset of CCSKs that do not harbor either the BCOR ‐ITD or YWHAE–NUTM2 translocation and lack known molecular alterations. Herein, we report the first case of CCSK arising in HSK and harboring epidermal growth factor receptor ITD.